Unveiling the eutrophication crisis: 20 years of nutrient development in Zhanjiang Bay, China - Liang, Haorui; Zhang, Junxiao; Zhang, Jibiao; Zhang, Peng; Deng, Xue; Chen, Jiyu; Wang, Zhiliang; Long, Chao; Lu, Chuqian; Wang, Di; Liang, Yuzhao (Frontiers in Marine Science, 2024)
Coastal eutrophication is a major issue of marine pollution. The main factors controlling eutrophication must be identified to ensure effective marine environmental management according to the respective local conditions. Zhanjiang Bay (ZJB), located northwest of the South China Sea, is a semi-closed bay influenced by complex water flows and the development of surrounding cities. In this study, we investigated the development of nutrient concentrations and compositions in ZJB seawater over the past 20 years and the factors influencing eutrophication based on several field investigations from 2006 to 2022 and historical data. High concentrations of dissolved inorganic phosphorus (DIP) and dissolved inorganic nitrogen (DIN) were the main contributors to the severe long-term eutrophication in ZJB; however, light eutrophication was observed in the outer bay, primarily caused by chemical oxygen demand (COD) and DIP. The primary sources of COD and nutrients were riverine freshwater, sewage outfalls, mariculture and domestic effluents carried by rivers. Tidal effects diluted the nutrient concentrations in the bay with seawater from the outer bay, thereby playing a key role in nutrient redistribution. The DIN: DIP ratio of ZJB showed long-term nitrogen restriction and excess phosphorus, primarily owing to mariculture activities. Marine undertakings can exert various impacts on water quality. Eliminating illegal aquaculture and launching aquaculture tailwater treatment can improve water quality, whereas practices such as channel dredging may worsen it. This study demonstrates the intricate dynamics of the ZJB ecosystem and offers valuable insights for effective environmental management and conservation efforts.